Efektivitas Septic Tank Upflow dan Downflow Filter untuk Pengolahan Air Limbah Domestik - Novan Dwi Novembry; Anie Yulistyorini; Mujiyono Mujiyono (Direktorat Bina Teknik Permukiman dan Perumahan, 2022)
Domestic wastewater is one of the causes of water pollution that can affect the quality of clean water sources. The effectiveness of wastewater treatment using septic tanks is still not optimal because the design does not meet technical standards. Organic pollutants are still wasted in the surrounding environment. This study aims to determine the efficiency level of domestic wastewater treatment using a septic tank upflow filter and a septic tank downflow filter in reducing organic pollutants. The domestic wastewater used in this study was taken from the Janti Communal IPAL in Malang. The septic tank model used in this study was 54 x 22 x 37 cm, made of glass with a thickness of 5 mm, a flow rate of 20 litres/day, and a detention time of 2 days. The septic tank model consists of three compartments with a filter media thickness of 15 cm for each type. The efficiency of pollutant reduction in septic tank upflow filter processing is BOD 55.84%, COD 58.64%, TSS 87.84%, Ammonia 75.07%, and Total Coliform 57.19%. While in the septic tank downflow filter, the efficiency of BOD reduction was 65.26%, COD 66.90%, TSS 90.34%, Ammonia 79.52%, and Total Coliform 57.54%. Domestic wastewater treatment with a septic tank downflow filter resulted in a higher BOD, COD, TSS, Ammonia, and Total Coliform reduction efficiency than an upflow filter septic tank.